Resolution enhancement techniques in optical lithography - Wong, Alfred Kwok-Kit (SPIE Press, 2001)
Ever-smaller IC devices are pushing the optical lithography envelope, increasing the importance of resolution enhancement techniques. This tutorial encompasses two decades of research. It discusses theoretical and practical aspects of commonly used techniques, including optical imaging and resolution, modified illumination, optical proximity correction, alternating and attenuating phase-shifting masks, selecting RETs, and second-generation RETs. Useful for students and practicing lithographers.
Keywords: Integrated circuits -- Design and construction.; Microlithography.; elektronické knihy; electronic books